Development of WPI/Inulin Maillard Conjugate Based Nanoemulsion Delivery System to Enhance the Bioaccessibility of Lycopene - Lee, Se Hee; Kim, Yeon Woo; Lee, Won Jae (Journal of Agriculture & Life Science, 2024)
This study investigated the effect of manufacturing variables (including heating temperature) on the physicochemical properties of nanoemulsion delivery system (NDS) prepared with WPI/Inulin Maillard conjugate and to study how the physicochemical properties of NDS affected the bioaccessibility of lycopene. The functional properties of the WPI/Inulin Maillard conjugate were determined using the OPA method, interfacial tension, and EAI. The physicochemical and morphological properties of NDS were measured using Zetasizer and TEM, respectively. The bioaccessibility of lycopene in the WPI/Inulin Maillard conjugate based NDS was measured using a spectrophotometer. As the pH and heating temperature increased, the Maillard conjugation efficiency increased significantly (p<0.0001). The emulsifying properties of the WPI/Inulin Maillard conjugate were greater than those of WPI. A WPI/Inulin Maillard conjugate based NDS with a size of ~180 nm was observed in TEM images while the droplet size of the WPI/Inulin Maillard conjugate based NDS was smaller than that of the WPI based NDS. During in vitro digestion, no significant changes in the droplet size and PDI of NDS were observed in the mouth and stomach phases, whereas in the intestinal phase, the droplet size and PDI increased significantly (p<0.0001). Moreover, the bioaccessibility of lycopene in the WPI/Inulin Maillard conjugate based NDS significantly increased (p<0.0001), compared with that of the WPI based NDS. There was a significant (p<0.05) increase in the bioaccessibility of lycopene with a decrease in the interfacial tension and droplet size of NDS. In conclusion, WPI/Inulin Maillard conjugate based NDS can be used to enhance the bioaccessibility of lycopene.